Empowerment Of Cadres Caring For Stunting Among Pregnant Women - Elly Wahyuni; Tonny Cortis Maigoda; Mariati; Rialike Burhan; Dina Anggraini (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Stunting remains a global and national health issue. In Seluma Regency, the prevalence of stunting increased from 21.1% (2022) to 24.4% (2023), with Sukaraja District contributing the highest number of cases. One strategy for addressing this issue is empowering health cadres as agents of change in education and early detection of stunting among pregnant women. The general objective of this community service activity was to improve the knowledge of cadres and pregnant women regarding early detection of stunting risk during pregnancy as an effort to reduce stunting cases in Cahaya Negeri and Sidoluhur Villages, Sukaraja District, Seluma Regency. The activities were carried out in these villages from January to October 2025. The implementation methods included preparation, execution, and evaluation stages. The main activities consisted of cadre training using lectures, group discussions, role plays, demonstrations, and early stunting detection simulations. Evaluation was conducted through pre- and post-tests. Empowering cadres to care about stunting among pregnant women significantly increased their knowledge and skills in stunting prevention. The average cadre knowledge score increased from 80.75 (pre-test) to 92.5 (post-test), an increase of 11.75 points. The program also resulted in the establishment of stunting care cadre organizations in both villages, serving as a forum for continuous discussion and education. This empowerment program effectively enhanced cadres’ capacity in early detection of stunting risk during pregnancy and is expected to continue with support from the local government and health centers.